Prevalence of Psychological Co-morbidities among medical and dental students of a Medical University of Nepal (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: Medical and Dental students are vulnerable to higher levels of Psychological distress than other age matched peers. This study was carried to identify prevalence of depression and anxiety in medical and dental students. Material and Method: A cross sectional study was done among medical and dental students (2nd year to interns) of BPKIHS. A total of 600 students were enrolled through systematic random sampling and 588 (98%) responded. Semi-structured questionnaire was used to record socio-demographic variables along with Becks Depression Inventory(BDI) and Becks Anxiety Inventory(BAI). Results: The mean age of participants was 22±2years among which 61.2%(360) were male, 69.7%(410) were from medical faculty, 90.5%(532) were Nepalese and 9.5%(56) were Indians. Depressive symptoms was recorded in 25.3%(149) out of which 12.6%(74), 6.5%(38), 5.3%(31), 0.5%(3), 0.5%(3) had mild, borderline, moderate, severe and extreme depressive symptoms respectively. Similarly anxiety was recorded among 7.8%(46) students with 42 having moderate and 4 having severe anxiety symptoms. Among the participants 6.3%(37) had suicidal thoughts and 4(0.7%) of them had suicide attempt in last one year. Conclusion: Medical and dental students showed high prevalence of anxiety and depression even with suicidal thoughts including past attempt.